2016
DOI: 10.1038/cddis.2015.399
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the MAP3 kinase Tpl2 protects rodent and human β-cells from apoptosis and dysfunction induced by cytokines and enhances anti-inflammatory actions of exendin-4

Abstract: Proinflammatory cytokines exert cytotoxic effects on β-cells, and are involved in the pathogenesis of type I and type II diabetes and in the drastic loss of β-cells following islet transplantation. Cytokines induce apoptosis and alter the function of differentiated β-cells. Although the MAP3 kinase tumor progression locus 2 (Tpl2) is known to integrate signals from inflammatory stimuli in macrophages, fibroblasts and adipocytes, its role in β-cells is unknown. We demonstrate that Tpl2 is expressed in INS-1E β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Chronic inflammation is known to exert toxic effects on β cell survival and function (Cnop et al 2005, Varin et al 2016. In order to evaluate the positive impact of the reduction of inflammation on the secretory function of islets, we measured the glucose-induced insulin secretion (GIIS) during static incubation experiments.…”
Section: Lithium Treatment Improves the Glucose-induced Insulin Secrementioning
confidence: 99%
“…Chronic inflammation is known to exert toxic effects on β cell survival and function (Cnop et al 2005, Varin et al 2016. In order to evaluate the positive impact of the reduction of inflammation on the secretory function of islets, we measured the glucose-induced insulin secretion (GIIS) during static incubation experiments.…”
Section: Lithium Treatment Improves the Glucose-induced Insulin Secrementioning
confidence: 99%
“…Ex-4, as a glucagon-like peptide-1(GLP) receptor agonist, can effectively down-regulate blood glucose level, stimulate pancreatic β-cell regeneration, induce transcription of pro-insulin gene and promote maturation and secretion of insulin (31). Ex-4 can also stimulate the growth and proliferation of human β-cells, and suppress cytokine-induced apoptosis (32). Fanet al (33) demonstrated that Ex-4 could inhibit the apoptosis of retinal cell, balance the ratios of Bcl-2/Bax and Bcl-xL/Bax and decrease retinal reactive gliosis in diabetic Goto-Kakizaki rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated TPL2 in controlling inflammatory responses in non-hematopoietic cells that drive the pathogenesis of chronic inflammatory diseases, including neuroinflammation, lung inflammation, obesity-associated chronic inflammation, pancreatitis, hepatic inflammation and vascular inflammation 26 - 30 . Moreover, TPL2 is also implicated in the onset and progression of several inflammatory-related autoimmune diseases, including diabetes, multiple sclerosis (MS), rheumatoid arthritis (RA), inflammatory bowel disease (IBD), and thrombocytopenia (ITP) 31 - 35 . Collectively, these studies propose the importance of TPL2 kinase in propagating chronic inflammation that might drive malignant transformation through the production of inflammatory cytokines and the activation of various inflammatory and oncogenic signaling pathways.…”
Section: Tpl2 and Tumor-promoting Inflammationmentioning
confidence: 99%